The Search Benefits of Autonomous Mobility in Distributed Sensor Networks - Thomas A. Wettergren; C. Michael Traweek (International Journal of Distributed Sensor Networks)
We consider a problem of finding the effectiveness of applying varying amounts of motion in fields of autonomous unmanned vehicles performing group search operations. These fields are typically deployed to provide extended coverage over that provided by a single sensor in spatially extended search regions. The autonomous nature of these distributed sensing assets is attributable to constraints on communications bandwidth and manpower. Due to the potential large cost discrepancy between fielding moving searchers and fixed searchers, the potential benefit of searcher motion relative to that achievable by deployment of larger numbers of fixed nodes is a critical operational consideration. We build a parametric analytical model of searcher performance for fields of moving searchers, and through a perturbation analysis examine the effectiveness of searcher motion vice nonmotion in terms of numbers of searchers required to achieve similar goals. Numerical simulations support the conclusions that are obtained.